Performance and Economic Analysis of Multi-Rotor Wind Turbine - Sandhu, Navjot Singh; Chanana, Saurabh (Politeknik Elektronika Negeri Surabaya (PENS), 2018)
Power production of a wind turbine is dependent upon its rotor size and at present wind turbines with large rotor diameter (>175 m) are available in the market. However major problems associated with such large size conventional turbines are their cost & noise pollution. Due to these reason researchers have diverted their attention towards lower sized equivalent multi-rotor wind turbines. These turbines are found to be cheaper and good performers. Keeping it in view, in this paper an effort has been made to compare the energy yield and economics of two types of wind turbines i.e. single rotor & multi rotor wind turbine. Power, energy and cost models as proposed are used to determine the annual energy yield and economics of multi-rotor turbines. Simulation results as presented in this paper justify the suitability of multi-rotor wind turbine in place of single rotor configuration. Such turbines deliver more energy yield with low installation cost in contrast to single rotor turbines.